MULTIDOOR COURTHOUSE SYSTEM: AN ASSERTION FOR THE PROCEDURAL IMPROVEMENT AND COMBATING JUDICIALISATION (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
This article aims to bring the study of the mechanism "multi-door forum", which a priori is considered as one of the possible ways to combat and prevent the crisis of exacerbated access to the judiciary, either by dissatisfaction of citizens with their needs, or for the slowness in meeting their demands. The idea comes from the need to make procedural changes. This theme will be approached as a search to solve conflicts not only through the ordinary ways, but also through the extrajudicial way, because in some cases, precipitously in matters involving family law or, also, hypotheses in which there are alterations of institutional understandings, these are the fastest and most efficient. There is a need to change the thinking of the courts and their prosecutors, since while there is an incentive for alternative resolution, it is sometimes thought that these options are not as effective as the judicial route, which entails the numerous distributed processes. The bibliographic and documentary research was used, as well as the quantitative and qualitative method for the analysis of the obtained data.